Proton conductors, electrolyte membranes, membrane electrode assemblies, electrochemical cells and fuel cell stacks
The proton conductor with the BaZr (1-x-y)Yb x Sc y O 3-δ formula, synthesized via specific methods, addresses the need for improved conductivity by achieving higher proton conductivity, particularly when x=0.2 and y=0.1, suitable for electrochemical cells and fuel cells.
Patent Information
- Application Number
- JP2022509316
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-25
- Filing Date
- 2021-01-20
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-01-20
AI Technical Summary
Existing proton conductors, despite increasing crystal grain size to lower resistance, still require improvement in proton conductivity.
The proton conductor is formulated with the chemical formula BaZr (1-x-y)Yb x Sc y O 3-δ, where 0
The new formulation achieves higher proton conductivity compared to conventional conductors, with optimal results when x=0.2 and y=0.1, and is suitable for use in electrochemical cells and fuel cells.
Smart Images

Figure 0007617572000002 
Figure 0007617572000003 
Figure 0007617572000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to proton conductors, electrolyte membranes, membrane electrode assemblies, electrochemical cells and fuel cell stacks. [Background technology]
[0002] As a proton-conducting electrolyte material, the chemical formula BaZr 1-x M x O 3-α There is known a perovskite-type complex oxide represented by the following chemical formula: In this chemical formula, M is a trivalent substitution element.
[0003] Patent Document 1 discloses a compound having the chemical formula BaZr 0.85 Y 0.15 O 3 or BaZr 0.85 Y 0.10 Sc 0.05 O 3 According to Patent Document 1, a proton conductor represented by the chemical formula BaZr 1-x M x O 3-α By adding Sc to the proton conductor represented by the formula (1), the crystal growth during sintering is promoted, and a proton conductor with a large crystal grain size is obtained. As a result, the proportion of the grain boundaries, which have a higher resistance than the grain interior, in the whole is reduced, and the resistance of the entire proton conductor is reduced. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-23883 A Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, Patent Document 1 discloses a proton conductor with reduced overall resistance by increasing the crystal grain size. However, in order to further reduce the resistance of the proton conductor, it is required to improve the proton conductivity of the proton conductor material itself.
[0006] An object of the present disclosure is to provide a proton conductor having high proton conductivity.
Means for Solving the Problems
[0007] The proton conductor according to the present disclosure contains a compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ where 0 < x < 0.5, 0 < y < 0.5, (x + y) < 0.5, and 0 < δ < 0.5 are satisfied.
Effects of the Invention
[0008] The present disclosure provides a proton conductor having high proton conductivity.
Brief Description of the Drawings
[0009] [Figure 1] FIG. 1 shows a cross-sectional view of a membrane electrode assembly according to Embodiment 2. [Diagram 2] FIG. 2 shows a cross-sectional view of an electrochemical cell according to Embodiment 3. [Diagram 3] FIG. 3 shows a fuel cell system according to Embodiment 4. [Figure 4] FIG. 4 is a flowchart showing an example of a method for manufacturing a proton conductor according to an example. [Diagram 5] FIG. 5 shows a procedure for fabricating an electrochemical cell using the proton conductor of Example 13.
Modes for Carrying Out the Invention
[0010] (Embodiment 1) The proton conductor according to Embodiment 1 has the chemical formula BaZr(1-x-y) Yb x Sc y O 3-δ It contains a compound represented by. Here, this chemical formula satisfies 0 < x < 0.5, 0 < y < 0.5, (x + y) < 0.5, and 0 < δ < 0.5.
[0011] As demonstrated in Examples 1 to 10 described later, since the mathematical formula: (x + y) < 0.5 is satisfied, the proton conductor according to Embodiment 1 becomes a dense body by firing. In the unlikely event that the value of (x + y) becomes 0.5 or more, cracks occur during pellet production, as demonstrated in Comparative Example 1 described later. Also, as demonstrated in Comparative Examples 2 to 8, a proton conductor having a combination of dopants other than Yb and Sc has a lower proton conductivity when compared with a proton conductor having the same dopant composition ratio and a combination of dopants of Yb and Sc. Here, "having the same dopant composition ratio" when comparing each other means that the molar ratio of the dopants in the proton conductor is the same.
[0012] As described above, the proton conductor according to Embodiment 1 containing the above compound has a higher proton conductivity when compared with a proton conductor having the same dopant composition ratio as the proton conductor according to Embodiment 1 and having a combination of dopants other than Yb and Sc.
[0013] Desirably, in the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ the mathematical formula: y ≤ x is satisfied.
[0014] As demonstrated by the comparison between Examples 1 and 2, the comparison between Examples 4 and 6, and the comparison between Examples 5 and 8 described later, when the mathematical formula: y ≤ x is satisfied, the proton conductor according to Embodiment 1 has a higher proton conductivity.
[0015] Also, desirably, in the chemical formula BaZr (1-x-y) Yb x Scy O 3-δ In this case, the mathematical expression: (x+y)≧0.15 is satisfied.
[0016] As demonstrated in Examples 1 to 10 described later, when the formula: (x+y)≧0.15 is satisfied, the proton conductor according to embodiment 1 has high proton conductivity.
[0017] More preferably, the chemical formula is BaZr (1-x-y) Yb x Sc y O 3-δ In this case, the mathematical expression: (x+y)≧0.25 is satisfied.
[0018] As demonstrated in Examples 4 to 10 described below, when the formula: (x+y)≧0.25 is satisfied, the proton conductor according to embodiment 1 has a higher proton conductivity.
[0019] Also preferably, the chemical formula is BaZr (1-x-y) Yb x Sc y O 3-δ In this case, the mathematical expression (x+y)≦0.35 is satisfied.
[0020] As demonstrated in Examples 1 to 8 described later, when the formula: (x+y)≦0.35 is satisfied, the proton conductor according to embodiment 1 has high proton conductivity.
[0021] Also preferably, the chemical formula is BaZr (1-x-y) Yb x Sc y O 3-δ In, the formula x≧0.15 is satisfied.
[0022] As demonstrated in Examples 6 to 10 described later, when the formula: x≧0.15 is satisfied, the proton conductor according to embodiment 1 has high proton conductivity.
[0023] More preferably, the formula is BaZr (1-x-y) Yb xSc y O 3-δ In this case, x=0.2 and y=0.1 are satisfied.
[0024] As demonstrated in Example 8 described later, when x=0.2 and y=0.1 are satisfied, the proton conductor according to embodiment 1 has the highest proton conductivity.
[0025] The proton conductor according to embodiment 1 can be synthesized by the citrate complex method, the solid-phase sintering method, the co-precipitation method, the nitrate method, or the spray granulation method.
[0026] The proton conductor according to the first embodiment has the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ The proton conductor according to the first embodiment may contain a compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ The proton conductor according to the first embodiment may contain a compound represented by the chemical formula BaZr in a molar ratio of 5% or more, or 20% or more. (1-x-y) Yb x Sc y O 3-δ By containing the compound represented by the formula: the proton conductor according to embodiment 1 can exhibit high proton conductivity.
[0027] The proton conductor according to the first embodiment has the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ The proton conductor according to the first embodiment may be composed of a compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ "Comprised of a compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δThe proton conductor according to the first embodiment contains a compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ When the proton conductor according to embodiment 1 is composed of a compound represented by the formula:
[0028] As an example, the proton conductor according to the first embodiment has the formula BaZr (1-x-y) Yb x Sc y O 3-δ The proton conductor according to the first embodiment may be substantially composed of a compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ "Comprised of a compound represented by the chemical formula BaZr" means that the proton conductor according to embodiment 1 is made of a compound represented by the chemical formula BaZr, excluding components contained as unavoidable impurities. (1-x-y) Yb x Sc y O 3-δ In this case, in the proton conductor according to the first embodiment, the proton conductor is composed only of a compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ The compound represented by the formula (I) may account for 95% or more in terms of molar ratio.
[0029] The proton conductor according to the first embodiment has the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ The proton conductor according to the first embodiment may further contain other components in addition to the compound represented by the formula (I). The proton conductor according to the first embodiment may further contain, as other components, for example, impurities generated in the process of synthesizing the above-mentioned compound.
[0030] The proton conductor according to embodiment 1 contains a compound having the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δThe average value of the crystal grain size of the compound represented by is, for example, 0.1 μm or more and 10 μm or less. Further, even when the average value of the crystal grain size is within the above range or even when it is smaller than 0.1 μm, the proton conductor according to Embodiment 1 can achieve high proton conductivity. Here, the average value of the crystal grain size can be determined, for example, by using the median diameter (volume basis) obtained from the measurement of the particle size distribution.
[0031] (Embodiment 2) FIG. 1 shows a cross-sectional view of a membrane electrode assembly 10 according to Embodiment 2. The membrane electrode assembly 10 includes an electrolyte membrane 11 and a first electrode 12. The first electrode 12 is provided on the first main surface 11a of the electrolyte membrane 11.
[0032] The electrolyte membrane 11 contains the proton conductor described in Embodiment 1 as an electrolyte material. The electrolyte membrane 11 may further contain another compound exhibiting proton conductivity other than the compound represented by the chemical formula BaZr (1-x-y) Yb x Sc y O 3-δ Examples of other compounds include compounds represented by the chemical formula BaZr 1-x1 M1 x1 O 3-δ compounds represented by the chemical formula BaCe 1-x2 M2 x2 O 3-δ or compounds represented by the chemical formula BaZr 1-x3-y3 Ce x3 M3 y3 O 3-δ Here, M1, M2, and M3 each contain at least one selected from the group consisting of Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Sc, In, and Lu, and 0 < x1 < 1, 0 < x2 < 1, 0 < x3 < 1, 0 < y3 < 1, and 0 < δ < 0.5 are satisfied. The electrolyte membrane 11 may further contain an electrolyte material other than the proton conductor.
[0033] The thickness of the electrolyte membrane 11 is, for example, 1 to 50 μm.
[0034] The first electrode 12 may, for example, mainly contain at least one of the following compounds: (i) A mixture of an electrolyte material contained in the electrolyte membrane 11, one or more metals selected from the group consisting of Co, Fe, Pt, and Pt, and Ni (i.e., a cermet). (ii) Lanthanum-containing composite oxides (iii) Barium-containing composite oxides (iv) Strontium-containing composite oxides
[0035] When the first electrode 12 mainly contains a certain compound, it means that the mass ratio of that compound in the first electrode 12 is the largest.
[0036] The first electrode 12 has a thickness of, for example, 1 to 1000 μm. When the first electrode 12 also serves as a support for the cell, the first electrode 12 desirably has a thickness of 100 μm to 700 μm. When a component other than the first electrode 12 serves as a support for the cell, the first electrode 12 desirably has a thickness of 10 μm to 50 μm.
[0037] In FIG. 2, the electrolyte membrane 11 and the first electrode 12 are in contact with each other. However, another layer may be provided between the electrolyte membrane 11 and the first electrode 12. An example of the another layer is a functional layer. The functional layer is a layer that promotes the movement of electrons or protons between the electrolyte membrane 11 and the first electrode 12. The functional layer is made of, for example, a composite of a cermet and a complex oxide.
[0038] The electrolyte membrane 11 is produced by, for example, a tape casting method, a spin coating method, a dip coating method, a sputtering method, or a PLD (Pulse Laser Deposition) method.
[0039] (Embodiment 3) FIG. 2 shows a cross-section of an electrochemical cell 20 according to a third embodiment.
[0040] The electrochemical cell 20 according to the third embodiment includes a membrane electrode assembly 10 and a second electrode 13. That is, the electrochemical cell 20 includes a first electrode 12, an electrolyte membrane 11, and a second electrode 13.
[0041] The membrane electrode assembly 10 is described in the second embodiment.
[0042] 2, in the electrochemical cell 20, a first electrode 12, an electrolyte membrane 11, and a second electrode 13 are provided in this order. That is, the electrolyte membrane 11 is sandwiched between the first electrode 12 and the second electrode 13. In other words, the electrolyte membrane 11 is provided between the first electrode 12 and the second electrode 13.
[0043] The electrochemical cell 20 according to the third embodiment may be used, for example, as a fuel cell. Thus, for example, the first electrode 12 may function as an anode and the second electrode 13 may function as a cathode.
[0044] When the second electrode 13 functions as a cathode, the second electrode 13 includes a composite compound. For example, the second electrode 13 mainly includes lanthanum strontium cobalt oxide. The second electrode 13 can be provided on the membrane electrode assembly 10 by, for example, a screen printing method.
[0045] 2, the second electrode 13 and the electrolyte membrane 11 are provided in contact with each other, but this is not limiting. Another layer may be provided between the second electrode 13 and the electrolyte membrane 11.
[0046] The other layer can be, for example, a functional layer, which is described in the second embodiment.
[0047] The electrochemical cell 20 may be used in fuel cells, electrochemical hydrogen pumps, hydrogen sensors and water electrolysis devices.
[0048] (Embodiment 4) FIG. 3 shows a schematic diagram of a fuel cell system 1000 according to a fourth embodiment.
[0049] The fuel cell system 1000 includes an electrochemical cell 20. The electrochemical cell 20 is described in the third embodiment.
[0050] In the fuel cell system 1000 according to the fourth embodiment, the electrochemical cell 20 is used as a fuel cell. In this case, the first electrode 12 functions as a fuel electrode, and the second electrode 13 functions as a cathode.
[0051] The fuel cell system 1000 further includes an oxidizing gas supply path 1024 and a raw material gas supply path 1023. The oxidizing gas supply path 1024 is connected to the second electrode 13 and the oxidizing gas supplier 1021. The raw material gas supply path 1023 is connected to the first electrode 12 and the raw material supplier 1022.
[0052] The electrochemical cells 20 are stacked to obtain a fuel cell stack 30. That is, the fuel cell stack 30 includes a plurality of electrochemical cells 20. The fuel cell stack 30 can provide high output. The fuel cell stack 30 is housed in a housing 1014.
[0053] The housing 1014 may be made of a heat insulating material. An oxidant gas is supplied to the first electrodes 12 of the stacked electrochemical cells 20.
[0054] Specifically, the oxidizing gas is supplied from an oxidizing gas supplier 1021 through an oxidizing gas supply path 1024 to the second electrodes 13 (ie, cathodes) of the multiple electrochemical cells 20.
[0055] At the second electrode 13, the following reaction (1) proceeds. O 2 +4H + +4e - →2H 2 O (1)
[0056] The oxidant gas is, for example, air.
[0057] The raw material is supplied from a raw material supplier 1022 through a raw material gas supply path 1023 to the first electrodes 12 of the multiple electrochemical cells 20 .
[0058] At the first electrode 12, the following reaction (2) proceeds. 2H 2 →4H + +4e - (2)
[0059] The raw material is, for example, hydrogen molecules.
[0060] The hydrogen may be produced by a reforming reaction. Alternatively, the hydrogen may be produced by water electrolysis.
[0061] In this manner, the fuel cell system 1000 operates and generates power.
[0062] (Example) The present disclosure will now be described in more detail with reference to the following examples and comparative examples.
[0063] <Proton conductor> As described below, in the examples and comparative examples, proton conductors and evaluation pellets using the same were produced. The characteristics of each proton conductor were evaluated using each evaluation pellet.
[0064] [Example 1] (Preparation of proton conductors) 4 is a flow chart showing an example of a method for producing a proton conductor according to an embodiment of the present invention.
[0065] The following materials were prepared as starting materials for the proton conductor. Ba(NO 3 ) 2 (Kanto Chemical Co., Ltd.) 0.100mol ZrO(NO 3 ) 2 2H 2O (manufactured by Kanto Chemical Co., Inc.) 0.085 mol Yb(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.005 mol Sc(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0066] The above starting materials were added to 1000 mL of distilled water and dissolved to obtain a mixed solution, and the mixed solution was stirred (S11).
[0067] Next, 0.3 mol of citric acid monohydrate (manufactured by Kanto Chemical Co., Inc.) and 0.3 mol of ethylenediaminetetraacetic acid (manufactured by Kanto Chemical Co., Inc.) were added to the mixed solution (S12). Hereinafter, "ethylenediaminetetraacetic acid" is referred to as "EDTA".
[0068] Next, aqueous ammonia (28% by mass, manufactured by Kanto Chemical Co., Inc.) was added to the mixed solution, and the pH of the mixed solution was adjusted to 7 using a pH meter (manufactured by Horiba, Ltd.) (S13).
[0069] Then, the mixed solution was stirred at a temperature of 90 °C (S14).
[0070] After the pH of the mixed solution was adjusted to 7, the temperature of the mixed solution was raised from 95 °C to 240 °C using a hot stirrer (S15). Then, the solvent (i.e., water) was evaporated from the mixed solution. In this way, water was removed from the mixed solution, and a solid was obtained.
[0071] After the obtained solid was pulverized in a mortar, it was degreased at a temperature of about 400 °C (S16). In this way, a powder was obtained.
[0072] Using a hydraulic pump (manufactured by Enapac Co., Ltd.) and a powder molding die having a diameter of 30 millimeters, the obtained powder was pressed into a columnar shape. In this way, a columnar molded product was obtained.
[0073] Thereafter, the obtained circular molded product was pre-sintered in an air atmosphere at 900° C. for 10 hours (S17). In this manner, a pre-sintered powder was obtained.
[0074] The calcined powder was then pulverized (S18). The pulverized powder was then transferred to a plastic container together with zirconia balls.
[0075] Then, 100 g of ethanol (manufactured by Kanto Chemical Co., Ltd.) was added to the plastic container. In this way, a mixed liquid was obtained. Next, the mixed liquid was pulverized in a ball mill for 96 hours (S19).
[0076] After the grinding with the ball mill, the mixture was dried using a lamp to remove the ethanol from the mixture (S20). In this way, a powder was obtained.
[0077] The obtained powder was sintered at 1200° C. for 5 hours in an air atmosphere (S21).
[0078] By the above procedure, the proton conductor according to Example 1 was produced.
[0079] (Preparation of pellets for evaluation) First, the powder of the proton conductor prepared by the above method was vacuum dried at 200° C. for 12 hours.
[0080] Next, the obtained powder was pressed into a cylindrical shape using a hydraulic pump (manufactured by Enerpac Co., Ltd.) and a powder molding die with a diameter of 30 mm, and further molded into pellets at a pressing pressure of 200 MPa using a cold isostatic press (manufactured by Sansho Industry Co., Ltd.).
[0081] The obtained circular pellets were sintered in an oxygen atmosphere at 1600° C. for 10 hours to obtain sintered pellets.
[0082] The obtained sintered pellet was cut into a disk shape with a thickness of approximately 500 μm using a low-speed cutter (Isomet 4000). In this way, the pellet for evaluation was obtained. Both sides of the pellet for evaluation were polished using a lapping film sheet with 3 μm abrasive grains.
[0083] Then, Ag paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) was applied to both polished surfaces of the evaluation pellet by screen printing. The applied Ag paste had a diameter of 10 mm.
[0084] Then, the evaluation pellets coated with the Ag paste were fired in an air atmosphere for 1 hour at 900° C. In this manner, the evaluation pellets according to Example 1 were produced.
[0085] (Evaluation of proton conductivity) The proton conductivity of the proton conductor was calculated from the resistance and thickness of the pellet using the evaluation pellet according to Example 1. The resistance of the pellet was measured based on the AC impedance method. The method for determining the proton conductivity is as follows.
[0086] Using a Solartron 1287 (manufactured by Solartron Analytical), an AC signal was applied to the pellet with an amplitude of 10 mV and a frequency range of 1 MHz to 0.01 Hz. The measurements were performed in a humidified hydrogen atmosphere at 400°C and 600°C. A Cole-Cole plot was then output. Based on the arc of the output Cole-Cole plot, the intersection point between the arc and the real axis was determined. The real axis is the axis where the Y-axis value in the Cole-Cole plot graph is 0. The intersection point on the high frequency side of the obtained intersection points was taken as the resistance of the pellet.
[0087] Based on the measured resistance and the thickness of the pellet, the proton conductivity of the proton conductor was calculated.
[0088] [Example 2] In Example 2, a proton conductor and evaluation pellets were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.085 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.005 mol
[0089] [Example 3] In Example 3, a proton conductor and evaluation pellets were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.080 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0090] [Example 4] In Example 4, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.075 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.015 mol
[0091] [Example 5] In Example 5, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.070 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol
[0092] [Example 6] In Example 6, a proton conductor and pellets for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.075 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.015 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.010 mol
[0093] [Example 7] In Example 7, a proton conductor and pellets for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.075 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.020 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.005 mol
[0094] [Example 8] In Example 8, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.070 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0095] [Example 9] In Example 9, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.060 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol
[0096] [Example 10] In Example 10, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.065 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.025 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0097] [Comparative Example 1] In Comparative Example 1, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.050 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.030 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol
[0098] [Comparative Example 2] In Comparative Example 2, a proton conductor and pellets for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O (manufactured by Kanto Chemical Co., Inc.) 0.070 mol Y(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol Sc(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0099] [Comparative Example 3] In Comparative Example 3, a proton conductor and pellets for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O (manufactured by Kanto Chemical Co., Inc.) 0.070 mol Lu(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol Sc(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0100] [Comparative Example 4] In Comparative Example 4, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.070 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.020 mol In(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.010 mol
[0101] [Comparative Example 5] In Comparative Example 5, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.060 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.020 mol In(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.020 mol
[0102] [Comparative Example 6] In Comparative Example 6, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.070 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol Lu(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0103] [Comparative Example 7] In Comparative Example 7, a proton conductor and a pellet for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.060 mol Yb(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol Lu(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol
[0104] [Comparative Example 8] In Comparative Example 8, a proton conductor and pellets for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O (manufactured by Kanto Chemical Co., Inc.) 0.070 mol Yb(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol Al(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0105] [Comparative Example 9] In Comparative Example 9, a proton conductor and pellets for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials for the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O (manufactured by Kanto Chemical Co., Inc.) 0.090 mol Sc(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.010 mol
[0106] [Comparative Example 10] In Comparative Example 10, a proton conductor and pellets for evaluation were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.080 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.020 mol
[0107] [Comparative Example 11] In Comparative Example 11, a proton conductor and a pellet for evaluation were produced in the same manner as in Example 1, except for the following item (1), and the proton conductivity was evaluated. (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.070 mol Sc(NO 3 ) 3 ·xH 2 O(2 < x < 6, manufactured by Kanto Chemical Co., Inc.) 0.030 mol
[0108] [Comparative Example 12] In Comparative Example 12, a proton conductor and a pellet for evaluation were produced in the same manner as in Example 1, except for the following item (1), and the proton conductivity was evaluated. (1) The starting materials of the proton conductor were changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O(manufactured by Kanto Chemical Co., Inc.) 0.090 mol Yb(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.010 mol
[0109] [Comparative Example 13] In Comparative Example 13, a proton conductor and an evaluation pellet were produced and the proton conductivity was evaluated in the same manner as in Example 1, except for the following item (1). (1) The starting material of the proton conductor was changed to the following materials. Ba(NO 3 ) 2 (manufactured by Kanto Chemical Co., Inc.) 0.100 mol ZrO(NO 3 ) 2 ·2H 2 O (manufactured by Kanto Chemical Co., Inc.) 0.080 mol Yb(NO 3 ) 3 ·xH 2 O (2 < x < 6, manufactured by Kojundo Chemical Laboratory Co., Ltd.) 0.020 mol
[0110] (Evaluation Results of Proton Conductivity) Based on Table 1, the results of the proton conductivity of the produced proton conductor will be explained.
[0111] First, comparing Example 8 shown by x = 0.20 and y = 0.10 with Comparative Examples 2, 3, 4, 6, and 8 having the same dopant composition ratio, the BaZr 0.70 Yb 0.20 Sc 0.10 O 3-δ of Example 8 showed the highest proton conductivity. Also, comparing Example 9 shown by x = 0.20 and y = 0.20 with Comparative Examples 5 and 7, the BaZr 0.60 Yb 0.20 Sc 0.20 O 3-δ of Example 9 showed the highest proton conductivity.
[0112] From these findings, it was predicted that a combination of Yb and Sc would be the best for any composition ratio as a dopant.
[0113] Next, BaZr 1-x-y Yb x Sc y O 3-δ The differences in the various composition ratios shown in Examples 1 to 10 and Comparative Example 1 will be explained below.
[0114] Among these, BaZr 0.50 Yb 0.30 Sc 0.20 O 3-δ Only in Comparative Example 1, indicated by , cracks were observed during the firing process when the evaluation pellets were made. When the ratio of Yb and Sc dopants was high, the amount of H that could be incorporated into the material was reduced. 2 The amount of dissolved O increases, causing the crystal lattice to expand. It is believed that dense pellets cannot withstand this expansion and the pellets break.
[0115] In other words, when the dopant ratio is increased, the crystal lattice also expands at the same time, so it is expected that cracks will occur in the same way in the region of (x+y)≧0.5.On the other hand, no cracks occurred in the pellets of the proton conductors of Examples 1 to 10, which are represented by (x+y)<0.5.
[0116] Furthermore, in Example 9, Comparative Example 5, and Comparative Example 7, where (x+y)≧0.4, cracks were observed in the pellets after evaluation. On the other hand, in Examples 1 to 8 and Example 10, where (x+y)<0.4, no cracks were observed even after evaluation, suggesting that expansion due to hydration was limited.
[0117] Next, Examples 1 and 2, which show (x+y)=0.15, Examples 4, 6, and 7, which show (x+y)=0.25, and Examples 5 and 8, which show (x+y)=0.30, are compared.
[0118] In either case, when x≧y, the proton conductivity is high at 400° C. and 600° C. In particular, when the doping amount of Yb is large compared to the doping amount of Sc, the proton conductivity is high.
[0119] Examples 6 to 10, which are represented by x≧0.15, have higher proton conductivity than Examples 1 to 5, which are represented by x<0.15.
[0120] Example 8, where x=0.2 and y=0.1, showed the highest proton conductivity.
[0121] The proton conductor of Comparative Example 10, which was doped with only Sc and not with Yb, had a lower proton conductivity at 400° C. and 600° C. than the proton conductor of Example 3, which had the same ratio of dopants (i.e., the value of (x+y)). Similarly, the proton conductor of Comparative Example 11, which was doped with only Sc and not with Yb, had a lower proton conductivity at 400° C. and 600° C. than the proton conductors of Examples 5 and 8, which had the same ratio of dopants (i.e., the value of (x+y)).
[0122] The proton conductor of Comparative Example 13, which was doped with only Yb and not with Sc, had a lower proton conductivity at a low temperature of 400° C. compared to the proton conductor of Example 3, which had the same dopant ratio (i.e., the value of (x+y)).
[0123] [Table 1]
[0124] <Electrochemical cell> (Preparation of electrochemical cells) With reference to FIG. 5, the preparation of an electrolyte membrane and an electrochemical cell using the same will be described.
[0125] (1) Preparation of electrolyte green sheet (see S100 to S102) First, an electrolyte ceramic slurry was prepared. The proton conductor (i.e., BaZr 0.70 Yb 0.20 Sc 0.10 O 3-δ The following ingredients were mixed: Proton conductor of Example 8 (BaZr 0.70 Yb 0.20 Sc 0.10 O 3-δ ) 50g Polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd.) 5g Butyl benzyl phthalate (Kanto Chemical Co., Ltd.) 1.25g Mixed solvent 40g
[0126] The mixed solvent consisted of butyl acetate (20 g, manufactured by Kanto Chemical Co., Ltd.) and 1-butanol (20 g, manufactured by Kanto Chemical Co., Ltd.) In this manner, an electrolyte ceramic slurry was prepared.
[0127] Next, a film made of the electrolyte ceramic slurry was formed on a support sheet made of a polyethylene terephthalate film having a thickness of about 50 μm by the doctor blade method. The film made of the obtained slurry was heated at a temperature of 80° C. to evaporate the solvent. In this way, an electrolyte green sheet was produced. The electrolyte green sheet had a thickness of about 21 μm.
[0128] (2) Preparation of electrode green sheets (see S200 to S202) An electrode ceramic slurry was prepared by mixing the following materials: Proton conductor of Example 8 (BaZr 0.70 Yb 0.20 Sc 0.10 O 3-δ ) 10g Polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd.) 5g Butyl benzyl phthalate (Kanto Chemical Co., Ltd.) 1.25g NiO (Sumitomo Metal Mining Co., Ltd.) 40g Mixed solvent 40g
[0129] The mixed solvent consisted of butyl acetate (20 g, Kanto Chemical Co., Ltd.) and 1-butanol (20 g, Kanto Chemical Co., Ltd.).
[0130] Next, a film made of the electrode ceramics slurry was formed on a support sheet made of a polyethylene terephthalate film having a thickness of about 50 μm by the doctor blade method. The film made of the slurry had a thickness of about 30 μm. The film made of the obtained slurry was heated at a temperature of 80° C. In this way, an electrode green sheet was produced.
[0131] (3) Sheet stacking (see S300 to S303) The electrolyte green sheet was cut to obtain one cut electrolyte green sheet. Then, the polyethylene terephthalate film was peeled off from the electrolyte green sheet. The cut electrolyte green sheet had a size of 140 mm x 140 mm. The electrode green sheet was cut to obtain one cut electrode green sheet. The cut electrode green sheet had a size of 140 mm x 140 mm.
[0132] A plurality of cut electrode green sheets were laminated to obtain a laminate. The laminate was then hot pressed. The hot pressing was carried out under conditions of 85°C and 13 MPa. In this manner, a first electrode was produced.
[0133] Further, one cut electrolyte green sheet was laminated on one main surface of the first electrode to obtain a laminate. The obtained laminate was then hot pressed. The hot pressing was performed under the conditions of 80°C and 13 MPa. In this manner, a compact was obtained.
[0134] The obtained molded body was further pressed at a pressure of 50 MPa (by Sansho Industry Co., Ltd.) to obtain a laminate. The thickness was almost unchanged and was about 700 μm.
[0135] The laminate was cut to a size of 20 mm x 20 mm.
[0136] Finally, the cut laminate was sintered in an air atmosphere at 1400° C. for 2 hours. In this manner, a membrane electrode assembly was produced. The membrane electrode assembly was an assembly of an electrolyte membrane and a first electrode.
[0137] (4) Formation of the second electrode (see S304 and S305) Furthermore, a second electrode was provided on the obtained membrane electrode assembly.
[0138] LSC paste (manufactured by Noritake Company Limited, composition La 0.6 Sr 0.4 Chief of Staff 3-δ ) was applied by screen printing to one of the main surfaces of the membrane electrode assembly where the electrolyte membrane was exposed. The applied LSC paste had a diameter of 10 mm. In this way, the precursor of the cell was obtained.
[0139] The cell precursor was then sintered in air at 950°C for 2 hours. In this manner, an electrochemical cell was fabricated that included a first electrode, an electrolyte membrane, and a second electrode. The first electrode functions as a fuel electrode. The second electrode functions as an air electrode.
[0140] (Electrochemical cell evaluation) Hydrogen and air were supplied to the electrochemical cell obtained by the above method, and a power generation test of the fuel cell was carried out.
[0141] The electrochemical cell was set in a fuel cell holder (manufactured by Chino Corporation) and placed in an electric furnace. The temperature of the fuel cell holder was raised to 700°C, and the fuel electrode (NiO-BaZr 0.70 Yb 0.20 Sc 0.10 O 3-δHydrogen gas humidified at 20°C was supplied to the fuel electrode at 100cc / min, and air gas humidified at 20°C was supplied to the air electrode at 100cc / min, respectively, and the reduction of the fuel electrode was carried out for 12 hours. Next, the temperature of the fuel cell holder was lowered to 600°C and held at 600°C for 1 hour, and electrochemical evaluation was carried out using a potentiogalvanostat (MODULAB XM ECS, manufactured by AMETEC).
[0142] For the electrochemical evaluation, the voltage of the fuel electrode and the air electrode was swept from the open circuit voltage to 0.4 V at 4 mV / sec, and the current-voltage curve and the current-output curve were obtained. The maximum output obtained was 0.23 W / cm 2 It was confirmed that an electric current could be extracted from the electrochemical cell. [Industrial Applicability]
[0143] The proton conductors according to the present disclosure may be suitable for use in electrochemical cells and fuel cells. [Explanation of symbols]
[0144] 10 Membrane electrode assembly 11 Electrolyte membrane 12 1st electrode 13 Second electrode 20 Electrochemical Cell 30 Fuel Cell Stack 1000 Fuel Cell System 1014 Case 1021 Oxidant gas supply 1022 Raw material feeder 1023 Raw material gas supply route 1024 Oxidant gas supply route
Claims
1. A proton conductor comprising: Chemical formula BaZr (1-x-y) Yb x S.C. y O 3-δ The compound represented by the formula: Here, 0<x<0.5, 0<y<0.5, (x+y)<0.5, and 0<δ<0.5 are satisfied. Proton conductor.
2. The formula: y≦x is satisfied; The proton conductor according to claim 1 .
3. The formula: (x+y)≧0.15 is satisfied; The proton conductor according to claim 1 or 2.
4. The formula: (x+y)≧0.25 is satisfied; The proton conductor according to claim 3 .
5. The formula: (x+y)≦0.35 is satisfied; The proton conductor according to claim 1 .
6. The formula: x≧0.15 is satisfied; The proton conductor according to claim 1 .
7. The formula: x=0.2 and y=0.1 is satisfied. The proton conductor according to claim 1 .
8. The proton conductor according to any one of claims 1 to 7, electrolyte membrane.
9. A membrane electrode assembly, The electrolyte membrane according to claim 8, and a first electrode provided on a first main surface of the electrolyte membrane; Equipped with Membrane electrode assembly.
10. 1. An electrochemical cell comprising: The membrane electrode assembly according to claim 9 , and Second electrode Equipped with The first electrode, the electrolyte membrane, and the second electrode are provided in this order. Electrochemical cell.
11. 1. A fuel cell stack comprising: A plurality of the electrochemical cells according to claim 10. Fuel cell stack.
Citation Information
Patent Citations
Mixed ion conductor and device using the same
JP2007197315A
Proton conductor
JP2009023883A
Electrode material for solid oxide fuel cell, and electrode for solid oxide fuel cell
JP2010282772A
Membrane electrode junction body and solid oxide fuel cell
JP2017188439A
Fuel cell system
JP2019021578A